KEPEMIMPINAN PEREMPUAN DI MASA KONTEMPORER DALAM PERSPEKTIF ISLAM - Siti Afifahtul Mukarromah; Erny Roesminingsih (STAI Ma'had Aly Al-Hikam Malang, 2022)
Leadership is one of the skills needed in the current era. A leader is someone who is believed to be able to influence and direct the people he leads to do what is his duty. Currently, all individuals can easily get an education and upgrade themselves through current technology. Thus, leadership skills are not difficult to learn. Through the available platforms, it will be easy for someone to learn. At present, the learning process is also not limited. Both from the upper, middle, to lower classes, have the right to learn. Not only that, both men and women have the right to learn leadership skills. Islam is rahmatan lil 'alamin. Islam is a blessing for all of nature without exception. Islam pays great attention to all aspects of human life, including the issue of women's leadership. The research method in this research is the systematic literature review, namely by analyzing journal articles and reference sources that are relevant to the research topic. Based on the results of analysis from several sources, it was stated that there was no prohibition on a woman being a leader.Keywords: Leadership, woman’s leadership, Islam